Ottoman-Polish Diplomatic Relations (15th–18th century). An An notated Edition of Ahdnames and Other Documents, Brill Leiden–Boston–Köln 2000 - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2001)
Review: Ottoman-Polish Diplomatic Relations (15th–18th century). An An notated Edition of Ahdnames and Other Documents, Brill Leiden–Boston–Köln 2000.